Zâd al-Muttaqîn Fî Tauhîd Rabb al-`Âlamîn Syaikh Abdus Shamad al-Palembani - Idrus al-Kaf (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
Zâd-Muttaqîn fi Tauhîd Rabb al-Âlamin is one of the most important works of Syaikh Abdus Shamad al-Palembani, an ulama and a great sufi, who has a huge role in Islamic development in Malay World during the 18th century. This was the only work of his describing completely about Wihdat Al-Wujud. Unfortunately, this work was not widely-recognized by Muslim society. This is because the script was not listed in the Arabic-malay cataloqs. This makes the writer is interested to do some research on this work.Using a single script editing and a standard edition method, this study is expected to result a new edition which will be easily understood by modern readers. Moreover, it will be reviewed the manuscript’s codicology aspects in order to reveal the trace of manuscript history well. This study is also hoped to be able to illustrate about the whole basic framework on his sufistic thingking, mainly if it was related to his thought in the past and previous works.This work was originally rewritten in 1868 by Haji Ma’ruf bin Haji Muhammad Hasyim. This research found that the process of rewriting of this work was carelessly done. The writer found some serious mistakes; the numbering of the pages, miswrite, and some grammatical mistakes. In this work, al-Palembani teaches the basic concept of Tauhid, and then build a doctrine of Wihdat al-wujud on it. - in this case - Wihdat al-Wujud al-Muwahhid. His doctrine was derived from two different concepts; al-Faidh and al-Zhill, which were later combined. The approach used to interpret this teaching was to combine the two different concepts of the scholars from two main streams of sufisms; philosophical and akhlaki mysticism. Keywords: Zâd al-Muttaqîn fi Tauhîd Rabb al-`Âlamîn, Syaikh Abdus Shamad al-Palimbani, Philological Approach